LEARNER’S STRATEGIES IN LEARNING ENGLISH VOCABULARY - Afifah Raihany (OKARA: Jurnal Bahasa dan Sastra, 2012)
Learning does not see time and place. Learning can be done by everyone, every time and everywhere. Generally, the effectiveness of learning depends on the ways or the techniques of learning. Every learner has different competence in learning. So, there may be some differences of learning strategy between one learner and others. This learner’s choice of learning strategies, of course, affect learning outcomes in term of level and rate of achievement. So, it is necessary for learners to know what specific steps they can take to improve their learning. Thus, the objective of learning can be achieved. As a teacher, we can motivate them by letting them can choose to make the most of the learning opportunities it presents. Therefore, motivating students to learn means not only stimulating them to take an interest in and see the value of what they are learning, but also providing them guidance about how to go about learning it.